The Struggle to Defend Minority Rights: The Role of Islamic Religious Counselor in the Realization of Religious Freedom - Rijal, Syamsul; Desky, Harjoni; Rozali, Ermy Azziaty; Yasin, Taslim H. M. (Al-Albab, 2024)
When the principle of tolerance is seen as an agreement on shared values, the forms of its practice can be diverse, even contradictory. On the other hand, the relationship between minority and majority groups in Indonesia continues to change over time, and this dynamic becomes a locus of control for the authorities. The government never ignores this problem. In addition to regulations, one of the facilities provided is the existence of Islamic Religious Counselors. The purpose of this study is to explain the role of Islamic religious counselors in realizing harmonious relations for minority groups in freedom of religion and belief. The research method used in this study is a qualitative method with descriptive analysis. The results of the study show the issue in understanding the extent to which the role of divine (heavenly) religious symbols is manifested in the social realm when the majority and minority groups of various religious believers interact with each other in a society, and when each different symbol touches each other intensely. Religious counselors can provide an important foundation for expressing religion amid diversity. The main thing that needs to be underlined is the moderate religious insight and attitude. This is what distinguishes a Islamic religious councelor from other religious figures although both convey religious messages through guidance and counseling activities. The efforts and roles of religious icouncelors are explained from the perspective of religious moderation, harmonization, and freedom of religion and belief. From the perspective of religious moderation, the councelors have a role as an agent of moderation, guardian of morals, and guardian of faith, while from the perspective of harmonization, the councelors have an informative and educative roles, the same thing also in realizing freedom of religion and belief.